2004
DOI: 10.1007/s00277-003-0748-4
|View full text |Cite
|
Sign up to set email alerts
|

Possible efficacy of lamivudine treatment to prevent hepatitis B virus reactivation due to rituximab therapy in a patient with non-Hodgkin's lymphoma

Abstract: We used regimens containing rituximab in the treatment of five hepatitis B virus surface antibody (HBsAb)-positive patients with non-Hodgkin's lymphoma (NHL). Serum levels of HBsAb were obtained and analyzed in four of these patients. Two patients were HBs antigen (HBsAg) positive. One of these HBsAg-positive patients was treated with lamivudine because the patient developed fulminant hepatitis from hepatitis B virus (HBV) infection prior to chemotherapy. However, none of the other patients were administered l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
4

Year Published

2006
2006
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 18 publications
1
52
0
4
Order By: Relevance
“…Various studies have shown that patients with chronic HBV infection are at risk of HBV reactivation during chemotherapy 7,11,[21][22][23][24][25] and recently, the use of rituximab has also been demonstrated to increase the rates of viral infection and viral reactivation. [11][12][13][14] In contrast, the risk of developing HBV-related liver complications after chemotherapy and immunotherapy in patients with past HBV (isolated HBcAb positive) infection has not been well studied. The results of the current study found the risk of HBV reactivation during the course of systemic chemotherapy to be low; only 1 (1.5%) of the 67 patients experienced reactivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown that patients with chronic HBV infection are at risk of HBV reactivation during chemotherapy 7,11,[21][22][23][24][25] and recently, the use of rituximab has also been demonstrated to increase the rates of viral infection and viral reactivation. [11][12][13][14] In contrast, the risk of developing HBV-related liver complications after chemotherapy and immunotherapy in patients with past HBV (isolated HBcAb positive) infection has not been well studied. The results of the current study found the risk of HBV reactivation during the course of systemic chemotherapy to be low; only 1 (1.5%) of the 67 patients experienced reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…11 Rituximab appeared to reduce the antibody to hepatitis B surface antigen (HBsAb), and thus might induce an immunological environment that allows for easy HBV reactivation. 12 Several case reports suggest that rituximab in combination with chemotherapy may increase the risk of HBV reactivation. 13,14 Of concern, there have also been reported cases of HBV reactivation in patients with past HBV infection (HBsAg negative, HBcAb positive) during the course of chemotherapy and/or immunotherapy, sometimes proving fatal.…”
mentioning
confidence: 99%
“…With the increasing prevalence of HIV infection, HBV reactivation has also been observed in HBV-infected subjects with advanced immune deficiency due to HIV infection [22][23][24][25][26][27]. Hepatitis due to HBV reactivation has not only been reported in HBsAg-positive patients, HBeAg-positive [6,[28][29][30] or HBeAg-negative [31][32][33][34][35][36][37][38][39][40][41] subjects who were treated with chemotherapy and transplantation but also in HBsAg-negative patients who had past HBV infection (hepatitis B surface antibody; antiHBs positive and hepatitis B core antibody; anti-HBc positive) [42][43][44][45][46][47][48][49], especially those treated with rituximab or alemtuzumab-containing chemotherapy [50][51][52][53][54][55].…”
Section: How Important Is the Problem?mentioning
confidence: 99%
“…In the transplant setting, such as bone marrow transplant [1-3, 19, 20, 61], heart transplant [62], and kidney transplant [63,64], the use of immunosuppressive therapy is mandatory to prevent graft rejection and HBV reactivation has been well characterized. Recently, the advance in therapies based on mechanisms that target critical molecular pathways of tumors has evoked considerable interest and among them, rituximab (anti-CD20) [50][51][52][53][54], alemtuzumab (anti-CD52) [55], infliximab (anti-TNF) [65], have been associated with HBV reactivation in HBsAg-positive as well as HBsAgnegative patients. These agents cause profound and longlasting immunosuppression, which may account for the risk of HBV reactivation following treatment.…”
Section: Chemotherapy or Immunosuppressive Therapy Related To Hbv Reamentioning
confidence: 99%
“…Cependant, dans tous ces cas d'infections virales, y compris pour l'infection à JC virus, le rituximab était prescrit en association avec d'autres molécules ou immunosuppresseurs, interdisant toute conclusion. Des réactivations virales dues au virus de l'hépatite B (HBV) ont également été rapportées sous rituximab [18][19][20][21] avec un risque de décès important [22]. Dans les quelques cas où le rituximab a entraîné une agammaglobulinémie, des infections bactériennes muqueuses ont été observées, requérant des traitements substitutifs par immunoglobulines polyvalentes [9,23].…”
Section: Anti-cd20 : Rituximabunclassified